The old success [large type] - Grimes, Martha (Grimes, Martha. Richard Jury mystery., 2019)
"When the body of a French woman washes up on a wild inlet off the Cornish coast, Brian Macalvie, divisional commander with the Devon-Cornwall police is called in. Who could have killed this beautiful tourist, the only visible footprints nearby belonging to the two little girls who found her? While Macalvie reexamines the scene in the Scilly Islands, inspector Richard Jury-twenty miles away on Land's End-is at The Old Success pub, sharing a drink with the legendary former CID detective Tom Brownell, a man renowned for solving every case he undertook. Except one. In the days following the mysterious slaying of the Parisian tourist, two other murders take place: first, a man is shot at a country estate, then a holy duster turns up murdered in Exeter Cathedral. Macalvie, Jury, and Brownell set out to discover whether these three killings, though very different in execution, are connected"--